2016
DOI: 10.14260/jemds/2016/672
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Profile of Acute Bacterial Meningitis in Adults in a Tertiary Care Hospital in North Kerala

Abstract: CONTEXTAcute Bacterial Meningitis (ABM) is a medical emergency requiring immediate diagnosis and treatment. The bacterial pathogens responsible for ABM may vary with time, geographic distribution, age and preceding medical and/or surgical conditions of the patient. Information regarding the changing trends in terms of aetiology and antibiotic susceptibility in a particular region is essential for the correct and timely management of ABM. AIMThis study was done to determine the bacterial pathogens responsible f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
2
0
0
Order By: Relevance
“…Among culture-positive CSF specimens, 52.9% [(9/17), 95% CI=29.4-76.5)] were gram-positive in this study consistent with studies from India (64.71%) [23], (66.18%) [30], Qatar (53%), and Tikur Anbessa and Yekatit 12 Specialized Hospitals (58.8%) 41.2%) [25]. In contrast, the rate of gram-negative bacterial isolates was 47.1% (8/17) (95% CI= 23.5-70.6) in this study which is lower than a study from Palestine (83.6%) [28] and in line with studies from India (35.29%) [23], (64.29%) [22], (28.8%) [30], Qatar (47%), Tikur Anbessa and Yekatit 12 Specialized Hospitals (41.2%) [25] and Felege Hiwot Referral Hospital (62.5%) [27].…”
Section: Discussionsupporting
confidence: 90%
“…Among culture-positive CSF specimens, 52.9% [(9/17), 95% CI=29.4-76.5)] were gram-positive in this study consistent with studies from India (64.71%) [23], (66.18%) [30], Qatar (53%), and Tikur Anbessa and Yekatit 12 Specialized Hospitals (58.8%) 41.2%) [25]. In contrast, the rate of gram-negative bacterial isolates was 47.1% (8/17) (95% CI= 23.5-70.6) in this study which is lower than a study from Palestine (83.6%) [28] and in line with studies from India (35.29%) [23], (64.29%) [22], (28.8%) [30], Qatar (47%), Tikur Anbessa and Yekatit 12 Specialized Hospitals (41.2%) [25] and Felege Hiwot Referral Hospital (62.5%) [27].…”
Section: Discussionsupporting
confidence: 90%
“…11,12 In present study, ABM was more in males than females and the male to female ratio was 1.4:1. This finding is in par with findings of studies of Singh AK et al, Manjiyil IJ et al 13,14 The most common age group observed in the study was 51-60 years, and community-acquired was the commonest cause of meningitis in present study. This is variable from place to place based on the age, prevalent predominant pathogen, and multiple factors.…”
supporting
confidence: 91%